Poly(lactic acid)/Organoclay Nanocomposite Fibers: Preparation, Characterization and Curcumin Natural Dyeing - Nitayaphat, Walaikorn; Jintakosol, Thanut (Asian Journal of Chemistry, 2018)
The aims of the present study were to use organoclay to improve the property of poly(lactic acid) (PLA) fiber in the dyeing process. Chitosans were used to modify montmorillonite (MMT) to produce organoclay. Poly(lactic acid) was melt-mixed with oganoclay using a twin-screw extruder to achieve a PLA/organoclay nanocomposite. The nanocomposite fiber was then prepared using single-screw extruder. The effects of organoclay on the structure, thermal and dyeing properties of the nanocomposite were also investigated. The results of dyeing show that the nanocomposite fiber was dyeable with natural dye extracted from curcumin. The colour strength was found to be dependent on the amounts of chitosan in the organoclay. The fastness properties such as wash fastness and light fastness were found to be similar to that in traditional fibers. Other properties such as thermal stability were also reported. This study demonstrates that poly(lactic acid) can exhibit natural dyeability through its preparation in nanocomposite form.